Characterization of Pt-doped WO 3 nanoparticles synthesized by flame spray pyrolysis - Samerjai T. (2014)
Undoped WO 3 and WO 3 nanoparticles doped with 0.25-1.0 wt.% Pt were successfully produced in a single step by flame spray pyrolysis (FSP) [1]. Tungsten (VI) ethoxide 5% w/v in ethanol 99.8% and platinum (II) acetylacetonate were used as W and Pt precursors respectively dissolved in ethanol. The undoped WO 3 and Pt-doped WO 3 nanoparticles were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy dispersive spectroscopy (EDS). The BET surface area (SSA BET) of the nanoparticles was measured by nitrogen adsorption. From BET measurement, SSA BET increased and d BET decreased with increasing Pt concentration from 0 to 1.0 wt.%. The morphology and accurate size of the primary particles were further investigated by high-resolution transmission electron microscopy (HRTEM). The crystallite size of undoped WO 3 spherical was found to be ranging from 5-20 nm and the crystallite sizes of 0.25-1.0 wt.% Pt-doped WO 3 spherical particles were found to be in the range of 5-20 nm. © (2012) Trans Tech Publications.